Yemen : Economic Monitoring Report - World Bank (Washington, DC, 2014)
Decelerating Gross Domestic Product, or GDP growth widening primary non-oil fiscal deficit persisting double digit inflation and rapidly dwindling current account surpluses characterize the weaknesses in the Yemeni economy. Decline in oil production is proving to be an important turning point in Yemen s economic development. With the annual growth of GDP projected around percent for the second year in a row Yemen s per capita GDP is set to decline again in 2005. Underlying primary non-oil fiscal deficit continued to widen to 27 percent of GDP in 2004, reflecting the poor resource mobilization efforts. Inflation has persisted near 12 percent annual rate in the last two years and the inevitable revisions to petroleum prices and introduction of general sales tax will call for tighter monetary management to contain inflation in 2005. The buffer of foreign exchange reserves that the government has built to US $ 5 billion from high oil prices by end 2004 (some months of imports equivalent), could only provide a temporary cushion against erosion of current account balance.